2007
DOI: 10.1080/01421590601034662
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to bridging content gaps in the clinical curriculum

Abstract: Background: In 2004-05 Tulane University School of Medicine implemented a longitudinal Interdisciplinary Seminar Series composed of small-group interactive exercises to address topics that are often overlooked during the clinical education of medical students. The series utilizes five adult learning principles. Methods: Each of 13 seminars is offered at a fixed time slot, repeated two to six times per year. Students are required to attend a minimum of five seminars, of their choice, during years three and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…CBL is used to impart knowledge in various fields in health care and various fields of medicine. The findings in this review showed that articles demonstrated the use of CBL in medicine, 2 , 4 7 , 9 , 10 , 12 14 , 18 21 , 24 26 , 30 , 33 , 34 , 36 , 37 , 39 44 , 46 , 48 62 , 64 67 dentistry, 8 , 15 , 16 , 22 , 23 , 28 pharmacology, 11 , 27 , 29 , 35 , 45 , 63 occupational and physical therapy, 31 ...…”
Section: Discussion and Reviewmentioning
confidence: 79%
“…CBL is used to impart knowledge in various fields in health care and various fields of medicine. The findings in this review showed that articles demonstrated the use of CBL in medicine, 2 , 4 7 , 9 , 10 , 12 14 , 18 21 , 24 26 , 30 , 33 , 34 , 36 , 37 , 39 44 , 46 , 48 62 , 64 67 dentistry, 8 , 15 , 16 , 22 , 23 , 28 pharmacology, 11 , 27 , 29 , 35 , 45 , 63 occupational and physical therapy, 31 ...…”
Section: Discussion and Reviewmentioning
confidence: 79%
“…It can also build a conceptual bridge between theory and practice [2] and has assisted students in getting ready for and doing well on clinical exams [1]. Encourages active learning and yields more beneficial results [7,8].…”
Section: Barriers To Cblmentioning
confidence: 99%
“…CBL is an active learning technique similar to problembased learning that involves small groups and focuses on solving a given problem. It stimulates active learning and produces a more fruitful outcome [7,8]. While PBL encourages students to acquire foundational knowledge as part of the clinical case investigation, CBL is effective for students who have already acquired this knowledge [9].…”
Section: Introductionmentioning
confidence: 99%
“…Small group interactive teaching has found an increasing role in medical education in the recent past (Vernon & Blake 1993;Jaques 2003;McParland et al 2004;Landry et al 2007;Srinivasan et al 2007). Some studies have found small group tutorials which have mainly been studied in the context of problem-based learning (PBL), to be superior to traditional lectures for deep learning, creating favourable student attitudes and performance in clinical examinations (Vernon & Blake 1993;Albanese 2000;McParland et al 2004).…”
Section: Introductionmentioning
confidence: 99%